PENYULUHAN FAKTOR RISIKO PENYAKIT KARDIOVASKULER DAN PEMERIKSAAN KADAR KOLESTEROL PADA MASYARAKAT DI KELURAHAN SERANGAN, DENPASAR SELATAN - Sarihati, I Gusti Agung Dewi; Dhyanaputri, I Gusti Ayu Sri; Bekti, Heri Setiyo (Poltekkes Kemenkes Denpasar, 2024)
Abstract High cholesterol conditions increase the possibility of excess cholesterol deposition on blood vessel walls, and is a major cardiovascular risk factor that increases the incidence of atherosclerotic disease in adults. The aim of this service is to provide education about risk factors for cardiovascular disease and check total cholesterol levels. The methods used in community service are counseling, pre-test and post-test. Check total cholesterol levels with a POCT device. The results show an increase in knowledge after being given counseling. Total cholesterol levels were checked on 50 people who attended, 33 people (66%) had normal cholesterol levels and 17 people (34%) had total cholesterol levels that were high or exceeded 200mg/dL. Of the 17 people, 13 of them were men and 4 were women. Of the 17 people who had high total cholesterol levels, 10 people (59%) had insufficient knowledge about preventing the risk of cardiovascular disease when carrying out the pre-test.Keywords: cardiovascular, total cholesterol, counseling